Are Food Policies in Colombia coherent? - Buritica Casanova, Alexander; Yomayuza, Karoll Valentina; Salas Betancourt, Daniela (CGIAR System Organization, 2023)
Food not only satisfies a basic need but also reflects cultural, economic, and sustainability aspects. From the farm to the table, every bite we take is influenced by a complex network of factors, ranging from agricultural practices to policy decisions.